Kekerasan Dalam Rumah Tangga pada Masa Pandemi Covid-19 di Tinjau dari Perspektif Etika Kristen - Sugiono, Sugiono (Kharisma: Jurnal Ilmiah Teologi, 2022)
Domestic violence (KDRT) is a universal social fact. But its existence has increased after the COVID-19 pandemic. This issue is increasing due to increased family burdens, stress, and economic hardship due to the loss of a portion of income / work which has the potential to trigger conflict within the family. In writing this paper, the author will use descriptive qualitative research methods, with research stages with a literature approach or literature study. Based on the results of the discussion, it can be found several roles of Christian ethics that must be played by the church in order to uphold justice and truth and minimize the occurrence of victims of domestic violence, especially during the Covid-19 pandemic. Some of these roles include: the church must carry out biblical teachings about Christian family life, the Church must also commit to visiting the homes of Christian family members, the Church must always provide guidance and counseling and the Church must also be able to instill important principles, namely the importance of parenting and education. in family. Kekerasan dalam rumah tangga (KDRT) merupakan fakta sosial yang bersifat universal.  Tapi keberadaannya semakin meningkat setelah ada pandemi COVID-19.  Isu ini meningkat dikarenakan meningkatnya beban keluarga, stres, dan kesulitan ekonomi akibat kehilangan sebagian penghasilan/pekerjaan berpotensi memicu konflik dalam keluarga.  Dalam penulisan karya tulis ini penulis akan menggunakan metode penelitian kualitatif deskritif, dengan tahapan penelitian dengan pendekatan pustaka atau studi literatur.  Berdasarkan hasil pembahasan maka dapat ditemukan beberapa peran etika kristen yang harus dimainkan oleh gereja dalam rangka menegakkan keadilan dan kebenaran serta meminimalisisr terjadinya korban kekerasan dalam rumah tangga khususnya di masa pandemi Covid-19.  Beberapa peran tersebut antara lain: gereja harus melaksanakan pengajaran yang Alkitabiah tetang kehidupan keluarga Kristen, Gereja juga harus berkomitmen untuk mengunjungi rumah anggota keluarga Kristen, Gereja juga harus senantiasa memberikan bimbingan dan konseling serta Gereja juga harus mampu menanamkan prinsip penting yaitu pentingnya pola asuh dan pendidikan dalam keluarga.  Kata Kunci: